Implementasi P5 Tema â€œSuara Demokrasiâ€™ di SMK Yayasan Pharmasi Semarang - Januarta, Ganda; Makarim, Sayoto; Setiadi, Sofyandanu (PGSD Universitas Muria Kudus, 2025)
This study was motivated by the importance of implementing the Pancasila Student Profile Strengthening Project (P5) in the Merdeka Curriculum, particularly the theme of â€œThe Voice of Democracy,â€ to equip students with practical experience in democracy. This study aims to describe the implementation of this theme at the Semarang Pharmacy Foundation Vocational School and analyze its suitability with the principles of project-based learning and democratic theory in education.The research method used a qualitative approach with interview techniques, non-participatory observation, and document analysis. The research subjects included the facilitator team, homeroom teachers, and students. Data analysis followed the Miles & Huberman model.The results show that SMK Yayasan Pharmasi has formed a team of facilitators consisting of guidance counselors, homeroom teachers, subject teachers, student affairs vice principals, and student council advisors. The activities are carried out in three stagesâ€”preparation, implementation, and evaluationâ€”all of which are student-centered. Most of the activities are student initiatives and involve almost all students. The entire process has implemented project-based learning and reflects democratic principles. However, several weaknesses were found, namely the low interest of students in being nominated as leaders and the difficulty of involving 12th grade students who are undergoing practical training in the election process. In addition, several democratic roles such as critics, opposition, legislature, and judiciary have not yet emerged in the implementation.